Impact of patient-centered communication on patient satisfaction scores in patients with chronic life-limiting illnesses: an experience from Kenya - Sirera, Betty; Naanyu, Violet; Kussin, Peter; Lagat, David (Frontiers in Medicine, 2024)
Background: Patient satisfaction remains a key area of interest worldwide; utilizing a patientcentered communication approach, particularly with patients with chronic life-limiting illnesses may be one way to achieve this. However, there is a dearth of empirical information on the effect of patient-centered communication strategies in patients with chronic-life limiting conditions in Kenya on patient satisfaction.The objective of this study was to assess the impact of patient-centered communication on patient satisfaction.We conducted our study at a tertiary teaching and referral hospital in Kenya. We utilized a quasi-experimental pre-test post-test study and engaged 301 adult medical in-patients with chronic life limiting conditions. We randomized them to receive patient-centered communication, and evaluated the change in patient satisfaction scores using an adapted Medical Interview satisfaction Scale 21 MISS 21Results: 278 out of 301 recruited participants completed the study. The baseline characteristics of the participants randomized to the control and intervention arms were similar. Although both the control and intervention groups had a decline in the mean difference scores, the intervention arm recorded a larger decline, -15.04 (-20.6, -9.47) compared to -7.87 (-13.63, -2.12), with a statistically significant mean difference between the two groups significant at -7.16 (-9.67, -4.46).Participants in the intervention arm were less likely to: understand the cause of their illness (p <0.001), understand aspects of their illness (p <0.001), understand the management plan (p <0.001), receive all the relevant information on their health (p <0.001), and to receive adequate self-care information (p <0.001). They were also less likely to acknowledge a good interpersonal relationship with the healthcare providers (p <0.001), to feel comfortable discussing private issues (p 0.004), and to feel that the consultation time was adequate (p 0.001).Contrary to expectation, patient-centered communication did not result in improved patient satisfaction scores. Further studies can evaluate factors affecting and explaining this relationship and assess intermediate and long-term effects of provision of a patientcentered communication in diverse global contexts.